Pengaruh Ukuran Perusahaan, Pertumbuhan Perusahaan, Free Cash Flow, Leverage, Profitabilitas dan Struktur Kepemilikan Terhadap Kebijakan Membayar Dividen - Anggraini, Dita Astuti Dyah; Wihandaru, Wihandaru (Jurnal Manajemen Bisnis, 2015)
This research is intended to analyze firm size, growth, free cash flow, leverage, profitability and ownership structure to the policy to pay dividend. The sample in this research is a manufacturing company listed on the Stock Exchange in 2011-2014. This research used purposive sampling method in determining the number of samples used. The data that be used is unbalanced panel and this data has 290 annual finance report.this research use logistic regression logistic model. The results of this research showed firm size, free cash flow and profitability affected positively and significantly on dividend paying probability. Growth and leverage affected negative and significantly. While ownership structure did not affect the quality of dividend paying probability.